Overcoming obstacles and maximizing opportunities : smaller economies and Western Hemispheric integration : report ([s.n.] [S.l.], 1997)
Assesses the problems confronting smaller economies as they move towards closer trade integration with their hemispheric neighbours. Recommends ways in which smaller economies can prepare themselves to participate fully in a hemispheric free trade area. Suggests the mechanisms and measures that could be implemented to facilitate the economic adjustments in these countries that will arise from more open trade and investment policies.
Copy located in the Office of the Secretary-General